An Autopsy Based Study on Death due to Burn Injuries - Siddiqi, Muhammed Marzan; Rahman, Kazi Golam Mukhlesur; Ahmed, Farzana; Sultana, Nahid; Saify, Md Evran; Pasha, Faisal Mohammed (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Burn injuries remain a major health concern nowadays and one of the leading cause of accidental death in Bangladesh. Death due to burn injuries is common in forensic practice but many a time it is very difficult to investigate the burn incident as the important evidences are destroyed. During autopsy evaluation of each victim who died due to burn injuries, the autopsy surgeon faces various challenges which include identification of the victim, determination the cause and manner of death, interpretation of temperature related arte fact like heat ruptures, heat haematoma etc. Objective: To determine the frequency and various types of burn injuries causing death of the victims along with analyzing the post-mortem findings and identify emerging trends in burn injury related tragic death. Methods: This cross-sectional descriptive study was conducted on 112 burn injured cases autopsied at Dhaka Medical College Hospital, Dhaka, Bangladesh from September 2024 to February 2025. During autopsy, deceased bodies were meticulously examined both externally and after dissection internally. Data were collected from inquest reports, chalan, death certificates (if the victim died at hospital) which included information on victim’s demographics along with the statement of the eye witness of the scene of incident and the autopsy findings of the autopsy surgeon. A standardized protocol was followed to ensure data accuracy and consistency. Results: Results revealed a predominance of female victims 59(52.7%) compared to 53(47.3%) of male burn injured victims. The common sources of burn injuries were accidental fire from house hold gas/kerosene stove (34.8%), mosquito coil (19.6%) etc. Apart from these others factors responsible for burn injuries were accidental burst of gas cylinders (36.6%), electric short circuit (26.6%), and accident in industrial chemical factories or warehouses (16.1%). Common post-mortem findings included organ congestion in 112(100%) cases, erosions/carbon particles in respiratory tract/lungs specially in inhalation burn in 99(88.4%) cases, escharotomy present in 48(42.85%) cases and involment of the epidermis/dermis of the skin in 112(100%) cases. Conclusion: This study reveals different causes of death due to burn injuries along with the postmortem findings. Even early intervention in the clinical management of severe burn cases, still give a grave prognosis and many a times complete recovery is a great challenge. Necessary steps and precaution are needed to be taken in order to prevent these various types of accidental burn incidences. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:53-58